Intrinsic electronic transport and thermoelectric power factor in n-type doped monolayer MoS2. (12th April 2018) - Zhao, Yinchang; Dai, Zhenhong; Zhang, Chao; Lian, Chao; Zeng, Shuming; Li, Geng; Meng, Sheng; Ni, Jun
Abstract: The electronic transport and thermoelectric properties in n -type doped monolayer MoS2 are investigated by a parameter-free method based on first-principles calculations, electron–phonon coupling (EPC), and Boltzmann transport equation (BTE). Remarkably, the calculated electron mobility μ ∼ 47 cm 2 V −1 s −1 and thermoelectric power factor σS 2 ∼ 2.93 × 10 −3 W m −1 K −2 at room temperature are much lower than the previous theoretical values (e.g. μ ∼ 130–410 cm 2 V −1 s −1 and σS 2 ∼ 2.80 × 10 −2 W m −1 K −2 ), but agree well with the most recent experimental findings of μ ∼ 37 cm 2 V −1 s −1 and σS 2 ∼ 3.00 × 10 −3 W m −1 K −2 . The EPC projections on phonon dispersion and the phonon branch dependent scattering rates indicate that the acoustic phonons, especially the longitudinal acoustic phonons, dominate the carrier scattering. Therefore, a mobility of 68 cm 2 V −1 s −1 is achieved if only the acoustic phonons induced scattering is included, in accordance with the result of 72 cm 2 V −1 s −1 estimated from the deformation potential driven by acoustic modes. Furthermore, via excluding the scattering from the out-of-plane modes to simulate the EPC suppression, the obtained mobility of 258 cm 2 V −1 s −1 is right in the range of 200–700 cm 2 V −1 s −1 measured in the samples with top deposited dielectric layer. In addition, we also compute the lattice thermal conductivity κ L of monolayer MoS2 using phonon BTE, and obtain a κ L ∼ 123 W m −1 K −1 at 300 K.